The Effect of Structured Dyadic Methods (SDM) towards Students’ Critical Thinking in Reading - Siti Hairunisah (Universitas Pendidikan Mandalika, 2018)
This research was aimed at finding out the effect of structured dyadic methods (SDM) towards students’ critical thinking in reading. The research was experimental research and design was used pre experimental design with pre-test and post-test. The population of study was the eighth grade students of SMP Muhammadiyah Mataram which consists of one class. The sample of this study was one class consists of 17 students as experimental group without control group. The method used was pre experimental research with one group pretest-posttest design. The technique in collecting data the students were given pretest, treatment and posttest. The data were analyzed by using t-test. The result showed that the Structured Dyadic Methods (SDM) has positive effect because t-test 3.903 ≥ t-table 2.120 in 0,05 percent level of significant. Based on the result of this investigation, it was proved that the null hypothesis (Ho) was clearly rejected. Therefore the alternative hypothesis (Ha) is accepted. Thus this study can be concluded there has significance effect of structured dyadic methods (SDM) towards students’ critical thinking in reading at eight grade students of SMP Muhammadiyah Mataram in academic year 2017/2018.